The Perception of Public Relation Profession in The Society: Example of Elazığ City - Tanyıldızı, Nural İmik; Ataykaya, Mehmet (My University, 2019)
A profession plays a vital role in the functioning of society. Profession connects people and produces a social hierarchy. A person’s self is constructed from social and role identities. The concept of public relations has shown many changes and developments since its first emergence. In every period, public relations have come up to date with different definitions. Turkish people in this region don't generally know what is the public relations. Even today, this problem persists. This study focuses on how people in society perceive the concept of public relations in Elazığ. Elazig is a city in eastern Turkey. The aim of the study is to reveal the perception of the term in public relations in society and its recognition. Survey method was used within the scope of the aim and survey questions were prepared. The survey consisting of 15 questions related to the public relations profession was applied to 400 people in the Elazig, which is more than 18 years old, determined by the random method. As a result of the analysis, the findings of the public relations profession in the community in Elazığ have different findings.
Keywords: Halkla İlişkiler; İstatistik ve Olasılık; Davranış Bilimleri